Diversity in Shade and Light Leaf Morphology in Beech Populations of South Rodopi Mountains - Stefanos Boutsios; Amaryllis Vidalis; George C. Adamidis; Seraphim Hatziskakis; Georgios Varsamis; Ioannis Tsiripidis; Paraskevi Karanikola; Aristotelis C. Papageorgiou (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)
The size and shape of tree leaves and their variation within the canopy are the result of both physiological plasticity and an overall adaptive strategy against unfavourable environmental conditions. In this study, diversity patterns at leaf morphological traits will be described within and among populations of trees with different phylogenetic background. Beech ( Fagus sp.) is a widespread tree in Eurasia, represented by two species; F. sylvatica in Europe and F . orientalis in eastern Europe and Asia. Both species appear in the Rodopi mountains, in southeast Balkans. Five beech populations were sampled in the southern slopes of Rodopi along a west–east gradient representing an established transitional zone between the two beech species. The diversity of six leaf traits was examined in shade leaves and leaves exposed to direct irradiation. Significant differences appeared among populations and among the two shading classes. Western beech populations consisted of trees with smaller leaves and fewer veins and were morphologically closer to F. sylvatica , while eastern populations seemed to be closer to F. orientalis . Shade leaves were constantly larger and less round than light leaves, probably due to different light harvesting strategies. The differences between populations were larger for shade leaves than for light leaves and presented a clear east–west trend, consistent to the differentiation pattern provided by previous genetic studies in the same region. Our results indicate that shade leaves probably maintain their size and shape independent from light irradiation and therefore may better express genetic differences among populations.